Chiral Co(III)(salen)-catalysed hydrolytic kinetic resolution of racemic epoxides in ionic liquids - Oh, CR; Choo, DJ; Shim, WH; Lee, DH; Roh, EJ; Lee, S; Song, CE (ROYAL SOC CHEMISTRY, 2003)
In the chiral Co(III)(salen)-catalysed HKR of racemic epoxides, in the presence of ionic liquids, Co(II)(salen) complex is oxidised without acetic acid to catalytically active Co(III)(salen) complex during reaction and, moreover, this oxidation state is stabilised against reduction to Co(II) complex which enables the reuse of the recovered catalyst for consecutive reactions without extra reoxidation.
Keywords: ASYMMETRIC CATALYSIS; TERMINAL EPOXIDES; COMPLEXES; EPOXIDATION; EFFICIENT; SYSTEM